Epigenetics and its implications for plant biology 2. The 'epigenetic epiphany': epigenetics, evolution and beyond. - Grant-Downton, RT; Dickinson, H (2006)
SCOPE: In the second part of a two-part review, the ubiquity and universality of epigenetic systems is emphasized, and attention is drawn to the key roles they play, ranging from transducing environmental signals to altering gene expression, genomic architecture and defence. KEY ISSUES: The importance of transience versus heritability in epigenetic marks is examined, as are the potential for stable epigenetic marks to contribute to plant evolution, and the mechanisms generating novel epigenetic variation, such as stress and interspecific hybridization. FUTURE PROSPECTS: It is suggested that the ramifications of epigenetics in plant biology are immense, yet unappreciated. In contrast to the ease with which the DNA sequence can be studied, studying the complex patterns inherent in epigenetics poses many problems. Greater knowledge of patterns of epigenetic variation may be informative in taxonomy and systematics, as well as population biology and conservation.